Creative Writing for EFL Classroom: Students’ Perception on Its Benefits - Mardiningrum, Arifah; Sistyawan, Yan Nisa Intan; Wirantaka, Andi (Journal of Languages and Language Teaching, 2024)
Within the English as a Foreign Language (EFL) context of higher education, there is a discernible emphasis on academic writing, often overshadowing the realm of creative writing. Nevertheless, creative writing remains a prevalent and integral component of EFL education. This study endeavors to scrutinize the perceptions of EFL students regarding creative writing and elucidate the potential benefits derived from its practice. Employing a qualitative approach, the research conducted in-depth interviews as its primary mode of data collection, engaging six students enrolled in an English Education Study Program in Indonesia. These students had actively chosen to participate in an elective course centered on literary works. The study's findings revealed nuanced perspectives among students, highlighting the intricacies associated with creative writing. Students perceive creative writing as intriguing, underscoring the necessity for its inclusion in higher education. Simultaneously, they acknowledge its potential difficulty and emphasize the importance of clarity in its instructional delivery. Furthermore, the research discerned that creative writing serves as a valuable tool for emotional expression, a conduit for the development of creativity and imagination, and a means to refine writing and language skills. The implications of these findings extend beyond the conventional realm of language mastery, emphasizing the multifaceted advantages that creative writing offers in an educational context. Consequently, educators in higher education are urged to deliberate and meticulously plan the incorporation of language in creative writing classes or activities. Recognizing and leveraging the broader educational benefits of creative writing can enhance the pedagogical approach, fostering a more comprehensive and enriching learning experience for EFL students.